Measurement of the differential cross-sections of prompt and non-prompt production of J/[psi] and [psi](2S) in pp collisions at √s = 7 and 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
The production rates of prompt and non-prompt J/ψ and ψ(2S) mesons in their dimuon decay modes are measured using 2.1 and 11.4 fb−1 of data collected with the ATLAS experiment at the Large Hadron Collider, in proton–proton collisions at s√=7 and 8 respectively. Production cross-sections for prompt as well as non-prompt sources, ratios of ψ(2S) to J/ψ production, and the fractions of non-prompt production for J/ψ and ψ(2S) are measured as a function of meson transverse momentum and rapidity. The measurements are compared to theoretical predictions.